The Effect of IT Governance Implementation on Decision-Making Performance (Case Study in PT XYZ) - Mahri, Annisa; Adrianto, Zaldy (Universitas Padjadjaran, 2024)
This study aims to determine the effect of IT governance implementation on decision-making performance. This study uses qualitative data and population of the research is from interview data with 5 respondents from PT XYZ in different divisions, which are Management Information System division, Finance division, and consultant. The data analyzed using Atlas.ti software for processing qualitative data. The results of the study show that the implementation of IT Governance at PT XYZ has a significant impact on decision-making performance by focusing on performance measurement and establishing clear KPIs for evaluation. Furthermore, the adoption of an ERP system allows all business units to function within an integrated framework, improving their ability to make quicker, more reliable, and data-driven decisions.